Gestational PFAS exposure and newborn size: The modifying effect of cord blood fatty acids - Chang Gao; Lin Luo; Yijun Fan; Liyan Guo; Lijuan Guo; Lin Tao; Fangbiao Tao; De-Xiang Xu; Robert A. Gibson; Maria Makrides; Hua Wang; Yichao Huang (Environmental Science and Ecotechnology)
Per- and polyfluoroalkyl substances (PFASs) can disrupt lipid metabolism, and changes in cord blood fatty acid composition have been observed in small newborns. Emerging evidence suggests that exposure to PFASs during pregnancy is linked to decreased newborn size, although the evidence is not consistent. The modifying effect of fatty acids on the associations of gestational PFAS exposure with newborn size is still unknown. Here we show that the nutritional status of the fetus, as indicated by the level of fatty acids in the cord blood, mitigates the adverse effects of gestational PFAS exposure on the size of the newborn. Our study confirms the adverse developmental effects of PFASs and identifies emerging short-chain PFASs as the primary drivers of reduced newborn size, despite their lower exposure burden compared to legacy PFASs. Additionally, we find the protective role of cord blood fatty acids, suggesting potential strategies for mitigating the detrimental effects of emerging environmental exposures on human health. Our findings provide new evidence of the potential toxicity of emerging PFASs and call for further toxicity evaluations of these pollutants for regulatory purposes. Future studies should consider the complex interaction between exposure and nutrition within the human body, particularly during the first thousand days of life, to promote lifelong health.